10‐Year Results of Therapeutic Ratio by Intensity‐Modulated Radiotherapy Versus Two‐Dimensional Radiotherapy in Patients with Nasopharyngeal Carcinoma. (6th August 2018) - Chen, Lei; Zhang, Yuan; Lai, Shu‐Zhen; Li, Wen‐Fei; Hu, Wei‐Han; Sun, Rui; Liu, Li‐Zhi; Zhang, Fan; Peng, Hao; Du, Xiao‐Jing; Lin, Ai‐Hua; Sun, Ying; et al.
Abstract: Background: The purpose of this study was to verify 10‐year results of survival and late toxicities and assess the ultimate therapeutic ratio of intensity‐modulated radiotherapy (IMRT) versus two‐dimensional radiotherapy (2DRT) in patients with nasopharyngeal carcinoma (NPC). Materials and Methods: We retrospectively reviewed the data from 1, 276 patients with nonmetastatic NPC who received IMRT or 2DRT from January 2003 to December 2006. Results: Of the 1, 276 patients, 512 were treated with IMRT and 764 with 2DRT. Median follow‐up was 115 months. At 10 years, the IMRT group demonstrated significantly better results than the 2DRT group in local failure‐free survival (L‐FFS; 90% vs. 84%; hazard ratio [HR], 0.57, 95% confidence interval [CI], 0.40–0.81; p  = .001), failure‐free survival (FFS; 69% vs. 58%; HR, 0.69, 95% CI, 0.57–0.83; p  < .001), and overall survival (OS; 75% vs. 63%; HR, 0.62, 95% CI, 0.51–0.77; p  < .001). Subgroup multivariate analyses showed that radiotherapeutic technique (IMRT vs. 2DRT) remained an independent prognostic factor for L‐FFS in the T1 subgroup (HR, 0.30; 95% CI, 0.11–0.80; p  = .02); for FFS in the stage II subgroup (HR, 0.42; 95% CI, 0.24–0.73; p  = .002); and for OS in the stage I (HR, 0.20; 95% CI, 0.04–0.96; p  = .04), stage II (HR, 0.39; 95% CI, 0.21–0.75; p  = .004), and stage IVA–B (HR, 0.74, 95% CI, 0.56–0.98; p  = .04) subgroups. The incidence of grade 3–4 temporal lobe necrosis, cranial neuropathy, eye damage, ear damage, neck soft tissue damage, trismus, and dry mouth was significantly lower in the IMRT group than in the 2DRT group. Conclusion: IMRT demonstrated an improved ultimate therapeutic ratio compared with 2DRT in patients with NPC after a 10‐year follow‐up, with significant improvement of L‐FFS, FFS, and OS and decrease in most late toxicities. Implications for Practice: The ultimate therapeutic ratio of intensity‐modulated radiotherapy versus two‐dimensional radiotherapy in patients with nasopharyngeal carcinoma is unclear. In this retrospective study of 1, 276 patients with nonmetastatic nasopharyngeal carcinoma with a follow‐up of 115 months, intensity‐modulated radiotherapy demonstrated an improved ultimate therapeutic ratio compared with two‐dimensional radiotherapy, with significant improvement of local failure‐free survival, failure‐free survival, and overall survival and decrease in most late toxicities and noncancer deaths. However, distant control remains insufficient with this treatment modality. Abstract : Radiotherapy is the primary treatment modality for nondisseminated nasopharyngeal carcinoma. Treatment with two‐dimensional radiotherapy transitioned to three‐dimensional conformal radiotherapy, and in particular to intensity‐modulated radiotherapy, is a step forward in the treatment of nasopharyngeal carcinoma. This article describes a long‐term follow‐up to verify ten‐year results of survival and late toxicities and to assess ultimate therapeutic ratio by intensity‐modulated radiotherapy versus two‐dimensional radiotherapy in patients with nasopharyngeal carcinoma.